UPAYA MENERAPKAN PENTINGNYA WORK-LIFE BALANCE PADA KARYAWAN MELALUI PSIKOEDUKASI - Putu Regina Sanjiwani Prakasa; Adelia Mutiara Deski; Nurmuliasneny Musa; Feneta Fidi Kirani; Nono Hery Yoenanto (Jurnal Abdi Insani, 2023)
Every change faced by the organization has an impact on business processes and all employees. The ability to adjust to these changes can be time-consuming and encourages employees to be able to divide work and personal life responsibilities. One concept that can explain this phenomenon is work-life balance. Work-life balance is how to create and maintain a healthy and supportive work environment, which will make employees have a balance between work and personal responsibilities. This research aims to provide education and promotional efforts to employees to be able to increase knowledge about work-life balance and efforts to create a balanced life between work and personal life. This study uses a psychoeducational program to increase knowledge of the importance of work-life balance and efforts to apply it with a problem-based learning approach. Psychoeducation was carried out through webinars which were attended by 50 participants. Data collection techniques using convenience sampling, and data analysis using the t test. The results showed that overall the implementation of psychoeducation was given a value of 80.14% where this score reflects the participants' positive appreciation of the implementation of psychoeducation. Then the results of the pre-test and post-test statistics showed that there were differences before and after being given psychoeducation (p-value 0.00 <0.05), the differences indicated an increase in participants' knowledge regarding psychoeducational material regarding work-life balance. Work-life balance is one of the phenomena that encourage individuals to be able to understand their condition actively, so that psychoeducation with a problem-based learning approach is effective in involving participants in solving problems and having the skills to be able to solve problems. Online psychoeducation using a problem-based learning approach has proven to be effective in increasing participants' knowledge about the importance of work-life balance and efforts to implement it.